Factors Affecting Nurse Response Time in Indonesian Hospital Emergency Installation: A Literature Review - Nurul Imam; Taufan Citra Darmawan; Siska Christianingsih; Khalifatus Zuhriyah Alfianti (Nursing and Health Sciences Journal (NHSJ), 2024)
The success of handling cases in the Emergency Department is very dependent on the nurse's response time. However, nurses' response time is greatly influenced by many factors. The purpose of writing this systematic review is to find out in detail the Factors That Affect the Response Time of Emergency Department Nurses in Indonesian Hospitals. The study was identified systematically by searching the database through the keywords "Response time AND nurses AND Factors AND Emergency Department Installation AND Indonesian Hospital" The results consist of several national and international journal data bases conducted research at Indonesian Hospital 16 articles. Eligible articles are selected according to inclusion criteria. This systematic review article is related to factors that affect the response time of nurses or emergency room health workers and is published in English or Indonesian based on the last 5 years of study (2020-2024). The instruments used in each study used a stopwatch, observation sheet and questionnaire to assess response time. The results of a review of this research article about nurse response time in the emergency room of Indonesian hospitals explain that the factors that can affect response time are 1). Age, 2). Priority of the patient or patient's condition, 3). Education, 4). Years of service service, 5). Nurse Skills Training, 6). Knowledge, and 7). Workload. Factors that affect internally are age, patient priorities or patient condition, education, service tenure, nurse skills training and external workload factors. It is hoped that the hospital can provide support and motivation to nurses to improve nurses' response time skills according to existing standards.